The Asian climate change issues in the era of the global knowledge economy: welfare economic framework for analyzing the post-Rio and post-Kyoto developments - Sardar,; M.N.Islam ,; Clarke, Matthew (Environmental Management Society, Malaysia, 2003)
This paper reviews the emerging and enduring policy issues arising from climate change and its ensuing economic consequences in Asia. There is now little doubt that one of the most important environmental management issues facing, not only Asia but the world, is climate change. In recognition of the seriousness of this threat, the global community has responded with international conferences and agreements, such as the Rio Earth Summit and the Kyoto Protocol. On the economic front, the emergence of the global knowledge economy is an influential phenomenon providing a new set of institutional frameworks for the operation of global and national economies which have implicit effects and management of global climate change. Within this paper, a welfare economic framework is adapted to analyze and evaluate the issues of climate change and to comment on policy options. Effective post-Rio and post-Kyoto responses depend on fully understanding how the Asian economy is currently developing and the current GHG emissions level, all analyzed within a welfare economics frameworks. A set of policy responses is therefore presented